Different risk genes contribute to clear cell and non-clear cell renal cell carcinoma in 1532 Japanese patients and 5996 controls. Issue 12 (5th January 2022) - Sekine, Yuya; Iwasaki, Yusuke; Aoi, Tomomi; Endo, Mikiko; Hirata, Makoto; Kamatani, Yoichiro; Matsuda, Koichi; Sugano, Kokichi; Yoshida, Teruhiko; Murakami, Yoshinori; Fukui, Tomohiro; Akamatsu, Shusuke; et al.
Abstract: Identifying causative genes via genetic testing is useful for screening, preventing and treating cancer. Several hereditary syndromes occur in patients with renal cell carcinoma (RCC). However, the evidence is from the European population; it remains unclear how the RCC-related genes and other cancer-predisposing genes contribute to RCC development in the Japanese population. A case-control study of 14 RCC-related genes and 26 cancer-predisposing genes was performed in 1563 Japanese patients with RCC and 6016 controls. The patients were stratified into clear cell RCC (ccRCC) or non-ccRCC (nccRCC). Gene-based analysis of germline pathogenic variants in patients with each subtype and cancer-free subjects was performed. Following quality control, 1532 patients with RCC and 5996 controls were analyzed. For ccRCC, 52 of 1283 (4.05%) patients carried pathogenic variants mainly in the cancer-predisposing genes such as TP53 ( P  = 1.73 × 10 −4 ; OR, 5.8; 95% CI, 2.2–15.7). Approximately 80% of patients with pathogenic variants in TP53 had p.Ala189Val that was specific in East Asian population. For nccRCC, 14 of 249 (5.62%) patients carried pathogenic variants mainly in the RCC-related genes such as BAP1 and FH ( P  = 6.27 × 10 −5 ; OR, Inf; 95% CI, 10.0–Inf). The patients with the pathogenic variants in the associated genes were diagnosed 15.8 years earlier and had a higher proportion of patients with a family history of RCC (OR, 20.0; 95% CI, 1.3–237.4) than the non-carriers. We showed different and population-specific contributions of risk genes between ccRCC and nccRCC in Japanese for improved personalized medicine.